Agricultural water security from the perspective of critical theory paradigm - Aligholi, Forough; Hayati, Dariush (Frontiers in Water, 2022)
Ensuring the security of freshwater resources is one of the most important drivers of the quality of social and environmental systems. In recent years, the security of water resources has faced various challenges. In other words, the water resources have become more vulnerable to threats and there is more concern about the sustainable development of socio-environmental systems. The significance of water security and associated concerns have led many researchers to conceptualize the water security and design indices to measure it. The worrying situation of the water security suggests that traditional philosophical paradigms, because of the way they look at man and nature, cannot be successful in solving the problems of agricultural water insecurity. In this regard, it is necessary to look for a new paradigmatic perspective to solve this crisis. In this paper, which was written using a review and analytical study, an attempt was made to examine and compare the concept of water security from the perspectives of positivism, constructivism, and critical theory. In addition, indicators of the critical theory paradigm were introduced and their ability to help conceptualize agricultural water security was explored from a critical theory perspective. The indicators of the critical theory paradigm include: inclusion, communication, cosmopolitanism and change. Also, the concept of agricultural water security from the perspective of critical theory is the emancipation of vulnerable farmers from various communicational, political, social, sexual, economic, and natural barriers. In this process, they will be able to freely participate in water decision-makings and be able to change the existing conditions to the desired conditions. Overall, the results showed that the critical theory paradigm, because of its point of view to the man and nature, as well as its goals of emancipation and change, could be a solution to the complex problems of agricultural water security.